NEW EXPANSIONS OF BOOLEAN FUNCTIONS ON EXCLUSIVE OR OPERATION IN LOGICAL SYSTEMS DESIGN - A. A. Prihozhy (Системный анализ и прикладная информатика)
The Boolean function expansions and representation forms which are based on exclusive or operation are a key facility for design, test and diagnosis of digital systems and computer programs. The Zhegalkin polynomials, ReedMuller expressions and functional binary decision diagrams are among them. In the paper, novel expansions and Boolean function representation forms that are constructed using the partial logic, minimization operation and exclusive or operation are proposed. They generalize the positive and negative Davio expansions, take into account the orthogonality conditions for the minimization operation products and provide the creation